Addressing triggering post zancolli lasso procedure - Mohd Zaim MR; Shalimar Abdullah; Parminder Singh Gill NS; Nur Azuatul AK (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
A claw hand causes disability as kinematics are affected due to hyperextension at the metacarpophalangeal joints. Zancolli lasso procedure is a simple tenodesis procedure which effectively lessens clawing to allow better grip. We present a56-year-old lady who had a history of trauma with progressive clawing of her left hand. She has been diagnosed with partially recovered incomplete lower trunk brachial plexus injury. She underwent successful Zancolli lasso procedures for all of her fingers but 8 months later, the patient developed triggering of the index and middle fingers. We experimented by releasing the adhesions in one finger and releasing the whole A1 pulley together with the lasso-ed flexor digitorum superficialis (FDS) in the other finger and the latter worked.We repeated the procedure in the index finger and the triggering resolved. Although both her index and middle fingers now have a flexor digitorum profundus (FDP) only (the FDS having retracted proximally), she did not have a recurrence of her clawing. We attributed the triggering due to increasing A1 pulley volume as well as contractures causing post-release functional positions.